2017
DOI: 10.5858/arpa.2017-0286-cp
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Testing in Head and Neck Carcinomas: Guideline From the College of American Pathologists

Abstract: Context Human papillomavirus (HPV) is a major cause of oropharyngeal squamous cell carcinomas, and HPV (and/or surrogate marker p16) status has emerged as a prognostic marker that significantly impacts clinical management. There is no current consensus on when to test oropharyngeal squamous cell carcinomas for HPV/p16 or on which tests to choose. Objective To develop evidence-based recommendations for the testing, application, interpretation, and reporting of HPV and surrogate marker tests in head and neck car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
498
3
16

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 446 publications
(556 citation statements)
references
References 231 publications
10
498
3
16
Order By: Relevance
“…[27][28][29] However, for HPV analysis, only p16 immunochemistry is recommended in the eighth edition of the AJCC TNM classification. [27][28][29] However, for HPV analysis, only p16 immunochemistry is recommended in the eighth edition of the AJCC TNM classification.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] However, for HPV analysis, only p16 immunochemistry is recommended in the eighth edition of the AJCC TNM classification. [27][28][29] However, for HPV analysis, only p16 immunochemistry is recommended in the eighth edition of the AJCC TNM classification.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be stressed that positive p16 by immunostaining is a surrogate marker of oncogenic HPV infection, and only HPV-specific tests provide definitive evidence [4,11,21]. Recently Bishop et al [22] found that the HPV-PCR (Hybrid Capture II) test correlated with p16 immunohistochemistry and HR-HPV in situ hybridization using FNA specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Most OPHPVSCC are small in size but often present initially with a large cystic lymph node metastasis [2][3][4]. It has a better prognosis than human papilloma virus (HPV)-negative oropharyngeal squamous cell carcinoma (SCC) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations